Rebuilding a House of Cards: Envisioning Sustainable Federal Housing Policy - Katherine L. Lewis (Washington University Journal of Law & Policy, 2011)
The Article discusses the need for a sustainable housing policy in the U.S. It mentions the Fair Housing Act of 1968 (FHA) enacted by the U.S. Congress to deter discrimination in house selling or leasing. It says that the said act was reinforced by the Community Reinvestment Act of 1977 (CRA), which expanded the mortgage financing for low-income and minority borrowers. It mentions that the U.S. financial future and economy depend on the development of a sustainable federal housing policy.
Keywords: Low-income housing – Law & amp; legislation; Home ownership; Subprime loans; Asset-backed financing; Financial institutions; Sustainable development; United States. Dept. of Housing & amp; Urban Development; Foreclosure; Housing policy; Community Reinvestment Act of 1977; Fair Housing Act of 1968